Analysis of Status Violations by Students Based on Abraham Maslow's Hierarchy of Needs Theory in the Context of Guidance and Counseling - Eka Lestari; Widya Firdausi Lasty; Ade Karunia Rizky Manurung (FKIP - Universitas Riau, 2026)
The phenomenon of student misconduct, such as truancy, tardiness, smoking, and similar behaviours, remains a common problem in secondary education. Although not classified as fatal juvenile delinquency, such behaviour indicates a crisis of character internalisation and unmet psychological needs among students. This article aims to analyse violations of student status using Abraham Maslow's Hierarchy of Needs Theory as a framework for understanding. The research method employed is qualitative, using two approaches: case studies and literature reviews to analyse relevant sources. The findings indicate that status violations can be viewed as manifestations of neglected basic needs, such as a sense of security, social acceptance, or self-esteem. Based on these findings, this article proposes a counselling service framework based on a humanistic approach focused on fulfilling students' needs comprehensively. This approach is expected to support the role of guidance counsellors in addressing deviant behaviour in a more empathetic, preventive, and solution-oriented manner. Further research suggests that schools need to create an environment that fosters a sense of safety, respect and social acceptance for all pupils, as a preventive measure against status violations.